The Reactions and Implications of the “Resolution of the Informbiro” in Kraljevo and its Surroundings - Virijević, Vladan A.; Trifunović, Nemanja F. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The conflict between Yugoslavia and the Informbiro was certainly noticeable in the area of the town of Kraljevo and its immediate surroundings, but not as much as in some other parts of Yugoslavia.  The Communist party in Žiča District did not have further divisions since the members of the Committee and main party organizations were mostly unique in realizing the line of the Central Committee of the Communist Party of Yugoslavia. There was a relatively small number of members who were excluded from the Party on charges of supporting the Informbiro Resolution, external policy of the Soviet Union, exalting the personality of Joseph Stalin or criticizing the policy of the Party and state government of Yugoslavia. Named “Informbiro people” by its ex fellow-fighters, these people were arrested, sentenced to hard labor that lasted for several years, put beyond the pale, disabled in the processes of education or work promotion. The conflict over the Informbiro Resolution also influenced the common citizens, particularly those emotionally related to Russia, namely to the USSR, whose number in Žiča District was certainly not small. The citizens of Kraljevo and the surrounding villages were frightened by the war, subjected to repression by the state security authorities, under constant pressure of taking part in realization of the five-year plan, burdened with various administrative measures during the difficult years of economic blockade, by the lack of basic means for living, crop failures due to catastrophic draughts. However, under such conditions, they achieved great success in the field of industrialization of the town, building traffic infrastructure and making the first steps toward the revival of agriculture through general farmers’ cooperative.
Keywords: Kraljevo and its surroundings; the Informbiro Resolution; the Communist party; the USSR; repression